Physical, chemical, and biological properties of white MTA with additions of AlF3 - Marciano, Marina Angélica; Camilleri, Josette; Lucateli, Ribamar Lazanha; Costa, Reginaldo Mendonça; Matsumoto, Mariza Akemi [UNESP]; Duarte, Marco Antonio Hungaro (Springer Nature, 2018)
Objectives: Addition of aluminum fluoride (AlF3) to MTA was tested to inhibit dental discoloration. Materials and methods: MTA Angelus with 0, 5, 15, and 45% AlF3 were tested. The set cements were characterized using scanning electron microscopy, energy-dispersive spectroscopy, and X-ray diffraction. Radiopacity and setting time were analyzed according to ANSI/ADA 57 and ASTM C266-08. Volume change was evaluated using volumetric micro-CT analysis. The pH and calcium ion release were assessed after 3 and 24 h and 28 days. Dental discoloration in contact with the cements was assessed after 24 h and 28 and 90 days of contact with bovine and human dentine. Tissue reaction to subcutaneous implantation in rats was examined after 30 and 60 days. Results: AlF3 altered the microstructure of MTA. The addition of 5% AlF3 did not significantly alter the radiopacity, setting time, and volume change (p > 0.05). pH and calcium ion release significantly increased with addition of AlF3 (p > 0.05). All the tested proportions of AlF3 prevented the dental darkening verified for MTA Angelus in bovine and human teeth. AlF3 did not interfere in inflammatory response of MTA in all periods of analysis; otherwise, lower amounts showed less intense inflammatory infiltrate. Clinical relevance: AlF3 prevents destabilization of bismuth oxide and consequent tooth darkening, frequently verified in clinical practice when using white MTA. Conclusions: The use of 5% of AlF3 in combination to MTA resulted in a cement that did not result in dental discoloration and did not affect significantly physical, chemical, and biological properties.
Keywords: Biocompatibility; Biomaterials; Cement; Color